2020
DOI: 10.1111/ans.16250
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer in younger adults from a Bi‐National Colorectal Cancer Audit registry

Abstract: Background: The incidence of colorectal cancer (CRC) in younger adults (<50 years old) is rising worldwide, at a rate of 1% per annum since mid-1980s. The clinical concern is that younger adults may have more advanced disease leading to poorer prognosis compared to their older cohort due to lack of screening. Therefore, the aim of this study is to assess the incidence and short-term outcomes of colorectal cancer in younger adults. Methods: This is a retrospective study from a prospectively maintained bi-nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…There is a growing concern worldwide about the increasing incidence of CRC in younger adults (below 50 years old). This trend has raised clinical concerns that younger adults may present with more advanced disease, leading to a poorer prognosis compared to older cohorts due to a lack of screening (15,16). Recent studies have reported that a younger age at diagnosis and receiving systematic therapies could potentially result in longer OS and DSS for CRC patients (17).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing concern worldwide about the increasing incidence of CRC in younger adults (below 50 years old). This trend has raised clinical concerns that younger adults may present with more advanced disease, leading to a poorer prognosis compared to older cohorts due to a lack of screening (15,16). Recent studies have reported that a younger age at diagnosis and receiving systematic therapies could potentially result in longer OS and DSS for CRC patients (17).…”
Section: Discussionmentioning
confidence: 99%
“…However, unregulated inflammation can cause significant damage to the body, and a chronic inflammatory state impedes immune infiltration and increases angiogenesis, providing an ideal environment for the growth and reproduction of cancer cells and promoting the generation and spread of cancerous lesions. Relapsing tumors aggravate the inflammatory response in the body and form a negative feedback loop that increases the risk of postoperative relapse in patients[ 31 - 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CRC in younger adults (<50 years old) is rising worldwide, which has been at a rate of 1% per annum since mid-1980s and nearly 2 times as high as that in older populations. 1 This trend raised clinical concerns that younger adults may have more advanced disease leading to poorer prognosis compared to their older cohort due to lack of screening. 2 The distribution of CRC is significantly different in regions all over the world.…”
Section: Introductionmentioning
confidence: 99%